2014
DOI: 10.1177/1744629514523158
|View full text |Cite
|
Sign up to set email alerts
|

Actual leisure participation of Norwegian adolescents with Down syndrome

Abstract: This article reports the actual participation in leisure activities by a sample of Norwegian adolescents with Down syndrome aged 14. Representing a first generation to grow up in a relatively inclusive context, they live with their families, attend mainstream schools, and are part of common community life. Leisure information was obtained in individual, structured parent interviews, and added to existing longitudinal data from a project following the sample. Generally, the leisure activity may be viewed as var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…In a study of the same cohort at the age of fourteen, parents reported that their children rarely had friends visiting at home (Dolva et al, ). The present study showed that the number of visiting friends had increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of the same cohort at the age of fourteen, parents reported that their children rarely had friends visiting at home (Dolva et al, ). The present study showed that the number of visiting friends had increased.…”
Section: Discussionmentioning
confidence: 99%
“…The social life of adolescents with intellectual disability involves a smaller number of friends and fewer close friendships than with adolescents without disabilities (Solish, Perry, & Minnes, ; Søderstrøm & Tøssebro, ; Tipton, Christensen, & Blacher, ). They spend less time with friends outside school than others (Melbøe & Ytterhus, ; Solish et al, ), and fewer friends visit them at home (D'Haem, ; Dolva, Kleiven, & Kollstad, ). Commonly, their friends also have a disability and have been considered a friend for a long time (McVilly, Stancliffe, Parmenter, & Burton‐Smith, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not engaging in these activities can elevate the risk of social exclusion because leisure activities outside the home are often designed for people without disabilities. Others also often select the leisure activities believed to be appropriate for a person with a disability (Dolva, Kleiven & Kollstad 2014).…”
Section: Participation For People With Intellectual Disabilitiesmentioning
confidence: 99%
“…Furthermore, compared with their non-disabled peers, children and youths with intellectual disabilities participate more in social activities at home (King et al 2013) and with adults (especially their parents) (Solish, Perry, and Minnes 2010), and with family and other persons with disabilities (Dolva, Kleiven, and Kollstad 2014). Even though more integrated school systems are found to have positive influence on the level of participation in leisure activities of children with disabilities (including children with intellectual disabilities) (Ullenhag et al 2012), physical proximity in the community alone does not appear to ensure social inclusion in peer activities and interactions (Solish, Minnes, and Kupferschmidt 2003).…”
Section: Leisure and Barriers To Participationmentioning
confidence: 99%